2019
DOI: 10.1021/acssuschemeng.9b04829
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Hierarchically Macroporous MIL-125 with High Specific Surface Area for Photocatalytic CO2 Fixation

Abstract: Highly ordered hierarchical macroporous metal–organic framework (MOF) materials (macroporous MIL-125) have been successfully synthesized through a solvent evaporation-induced self-assembly route in one step. The obtained macroporous MIL-125 showed an extremely high specific surface area with the Brunauer–Emmett–Teller surface area reaching up to 1083 m2/g. Moreover, macroporous MIL-125 exhibited ordered hierarchical porous structure and excellent ultraviolet absorption ability. At present, atmospheric chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 39 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…3). In addition, the high specific surface area of the composite (45.74 m 2 g -1 ), element polyvalence and the higher adsorption oxygen content could also lead to the improvement of photocatalytic performance [36,37].…”
Section: Xps Analysismentioning
confidence: 99%
“…3). In addition, the high specific surface area of the composite (45.74 m 2 g -1 ), element polyvalence and the higher adsorption oxygen content could also lead to the improvement of photocatalytic performance [36,37].…”
Section: Xps Analysismentioning
confidence: 99%
“…240 nm, Figure 2E), which may be attributed to modest shrinkage of template during crystallization. 36 Unlike om-NENU-3a, cm-NENU-3a grows into an irregular morphology (Figure S9B), although the precursor concentration in the PS template interstices is essentially the same as that in the synthesis of cm-NENU-3a. The difference is the introduction of the PS template and HCOONa for preparing the om-NENU-3a.…”
Section: Resultsmentioning
confidence: 95%
“…180 nm) of om -NENU-3a is slightly smaller than the diameter of the PS sphere ( ca . 240 nm, Figure E), which may be attributed to modest shrinkage of template during crystallization …”
Section: Resultsmentioning
confidence: 99%
“…[13] Li et al reported highly ordered hierarchically microporous MIL-125 with high specific surface area was used as the photocatalyst for atmospheric chemical fixation of CO 2 through CO 2 carbonylative coupling reactions under ultraviolet irradiation. [14] At present, the mainstream pore size regulation methods can be roughly divided into the following ways: in-situ synthesis, postsynthesis modification, interpenetrating regulation, auxiliary synthesis, and competitive ligand regulation. Among them, the first two strategies are most widely used.…”
Section: Regulation Of Pore Sizementioning
confidence: 99%